Postprocedural Antiplatelet Treatment after Emergent Carotid Stenting in Tandem Lesions Stroke: Impact on Stent Patency beyond Day 1 - Pop, R.; Hasiu, A.; Mangin, P.H.; Severac, F.; Mihoc, D.; Nistoran, D.; Manisor, M.; Simu, M.; Chibbaro, S.; Gheoca, R.; Quenardelle, V.; Rouyer, O.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Postprocedural dual-antiplatelet therapy is frequently withheld after emergent carotid stent placement during stroke thrombectomy. We aimed to assess whether antiplatelet regimen variations increase the risk of stent thrombosis beyond postprocedural day 1.MATERIALS AND METHODS: Retrospective review was undertaken of all consecutive thrombectomies for acute stroke with tandem lesions in the anterior circulation performed in a single comprehensive stroke center between January 9, 2011 and March 30, 2020. Patients were included if carotid stent patency was confirmed at day 1 postprocedure. The group of patients with continuous dual-antiplatelet therapy from day 1 was compared with the group of patients with absent/discontinued dual-antiplatelet therapy.RESULTS: Of a total of 109 tandem lesion thrombectomies, 96 patients had patent carotid stents at the end of the procedure. The early postprocedural stent thrombosis rate during the first 24 hours was 14/96 (14.5%). Of 82 patients with patent stents at day 1, in 28 (34.1%), dual-antiplatelet therapy was either not initiated at day 1 or was discontinued thereafter. After exclusion of cases without further controls of stent patency, there was no significant difference in the rate of subacute/late stent thrombosis between the 2 groups: 1/50 (2%) in patients with continuous dual-antiplatelet therapy versus 0/22 (0%) in patients with absent/discontinued dual-antiplatelet therapy (P = 1.000). In total, we observed 88 patient days without any antiplatelet treatment and 471 patient days with single antiplatelet treatment.CONCLUSIONS: Discontinuation of dual-antiplatelet therapy was not associated with an increased risk of stent thrombosis beyond postprocedural day 1. Further studies are warranted to better assess the additional benefit and optimal duration of dual-antiplatelet therapy after tandem lesion stroke thrombectomy.DAPTdual-antiplatelet therapySTstent thrombosis